GÜLŞENİ DİVANI VE TAHLİLİ - KULAT, ÖZLEM (Fırat Üniveristesi, 2010)
Bu çalışma 15. yüzyıl şairlerinden Gülşenî-i Saruhanî'nin hayatı, sanatı,divanının transkripsiyonlu metni ve tahlilinden meydana gelmiştir. Gülşenî-iSaruhanî de diğer şairler gibi edebiyatımızın geleneklerine bağlı kalmış; duygu,düşüncelerini bilinen kelime, mecaz ve mazmunlarla ifade etmiştir.Gülşenî-i Saruhanî Divanı üzerine yaptığımız bu çalışma, şairin kullandığıkelimeler, üslubu ve edebî sanatları kullanışı doğrultusunda, şairi ve şairinyaşadığı dönemi anlamamıza yardımcı olacaktır.Sonuç olarak, bu tezin amacı Eski Türk Edebiyatının önemli şairlerindenbiri olan Gülşenî-i Saruhanî'nin edebi kişiliği ve eserini edebiyat dünyasınatanıtmaktır.Anahtar Kelimeler: 15. Yüzyıl, Gülşenî-i Saruhanî, Divan, TranskripsiyonluMetin, Tahlil

The study consists of the life, art, the transcript and analysis of thecollected poems of Gülşenî-i Saruhanî who is one of the 15th century Turkishpoets. Gülşenî-i Saruhanî is like other poets, faithful to our literature?s traditions.The poet expresses his emotions and thoughts with known words, metaphors andidioms.This study on Gülşenî-i Saruhanî?s collected poems helps us to understandthe poet and his time of living. At this point; words, style and literary arts whichhe uses give us clues.In conclusion, the aim of this research work is introducing Gülşenî-iSaruhanî?s literary characteristic and his collected poems to literature wordbecause of being an important poet of old Turkish literarure.Key Words: 15th century, Gülşenî-i Saruhanî, Collected Poems, the TranscriptedText, the Analysis
Gülşeni Saruhani Divanı transcripted text the analysis
Keywords: Türk Dili ve Edebiyatı